Advanced NIR ratiometric probes for intravital biomedical imaging. (24th December 2021) - Huang, Haoying; Qiu, Ruijuan; Yang, Hongchao; Ren, Feng; Wu, Feng; Zhang, Yejun; Zhang, Hong; Li, Chunyan
Abstract: Near-infrared (NIR) fluorescence imaging technology (NIR-I region, 650–950 nm and NIR-II region, 1000–1700 nm), with deeper tissue penetration and less disturbance from auto-fluorescence than that in visible region (400–650 nm), is playing a more and more extensive role in the field of biomedical imaging. With the development of precise medicine, intelligent NIR fluorescent probes have been meticulously designed to provide more sensitive, specific and accurate feedback on detection. Especially, recently developed ratiometric fluorescent probes have been devoted to quantify physiological and pathological parameters with a combination of responsive fluorescence changes and self-calibration. Herein, we systemically introduced the construction strategies of NIR ratiometric fluorescent probes and their applications in biological imaging in vivo, such as molecular detection, pH and temperature measurement, drug delivery monitoring and treatment evaluation. We further summarized possible optimization on the design of ratiometric probes for quantitative analysis with NIR fluorescence, and prospected the broader optical applications of ratiometric probes in life science and clinical translation.